Aplicación y devolución de las percepciones pagadas en la importación de insumos y materia prima y su incidencia en la gestión de las empresas fabricantes de calzado de la ciudad de Trujillo. - Guzmán Benites, Yela Lizet (2014)
The present research “APPLICATION AND RETURN OF THE PERCEPTIONS PAID IMPORT COMMODITY AND RAW MATERIAL AND ITS IMPACT ON THE MANAGEMENT OF SHOE MANUFACTURERS IN THE CITY OF TRUJILLO ENTERPRISES” has as main purpose to show that the Payment Systems developed IGV , in this case the scheme perceptions affect the liquidity of companies , because advance payments are not automatically cleared and the return is subject to a cumbersome process that can last several months. In the development of this descriptive research method was used because the data were obtained by direct observation, as well as collects, selects and consolidates information. On the other hand , it has also been used a survey of importers of inputs and raw materials for the manufacture of footwear plants , to know what is the opinion held on Regime Perceptions of IGV and the use thereof. The main objective of the study is to determine the impact of the application and return perceptions paid as imported inputs and raw material in economic and financial management of footwear manufacturing companies in the city of Trujillo. The conclusion I have reached is that the importers of inputs and raw materials are not immediately available to pay perceptions , which , leads to a lack of liquidity in order to meet the obligations with suppliers and banks , besides having to follow a cumbersome procedure to request the return of perceptions in which it is possible that the tax authorities, in exercising its powers , decides to initiate an audit procedure , which if not carried out in a reasonable time could generate a significant contributor to the decline heritage whose effects may include expulsion from the market, since this could not have the money that is the subject of an application for repayment .